Indonesia-Germany Defense Diplomacy in Military Education Cooperation - Purnama, Rafiq; Swastanto, Yoedhi; Waluyo, Surryanto Djoko (Technium Social Sciences Journal, 2021)
Indonesia-Germany Defense Diplomacy was resulted a Defense Cooperation Agreement (DCA) in the form of a Defense Cooperation Memorandum of understanding (MoU). The MoU is as the basis for the implementation of the Bilateral Experts Talks Meeting which resulted a military education cooperation in the form of the Military Training Assistance (MTA) program. The MTA program is a German military education program which is offered to personnels of Indonesian Armed Forces (TNI) which is expected to increase the capability and professionalism of personnels of Indonesian Armed Forces (TNI) and increase Confidence Building Measures (CBMs) and Capacity Building for both countries. This research aims to analyze the Indonesian-German defense cooperation in the field of military education and to analyze the Indonesian-German defense diplomacy in military education cooperation. This research is structured using the theory of international cooperation, the theory of diplomacy, the theory of defense diplomacy, and the concept of defense cooperation. This research was conducted using a qualitative-descriptive method. Data collection techniques used are interviews and literature study. The results of this research are expected to be a description of Indonesia-Germany defense cooperation and solutions to the problems.